A Phenomenological Perspective of the Rise of Brutality in Indonesian Political Activities during the Joko Widodo Era - Siregar, Iskandarsyah (Budapest International Research and Critics University, 2024)
This article examines the increasing phenomenon of brutality in Indonesian political activities during the presidency of Joko Widodo. While President Jokowi's administration has achieved significant economic and infrastructural advancements, these successes are overshadowed by a troubling rise in political violence, intimidation, and repression. This study explores the manifestations of brutality, from physical violence during protests and elections to psychological intimidation through online harassment. The findings indicate that polarization, identity politics, and the centralization of power have contributed to the normalization of these violent tactics, posing a severe threat to Indonesia's democratic integrity. The article concludes by highlighting the urgent need for reforms to address this brutality, protect democratic institutions, and ensure a stable and inclusive future for Indonesia.